Thoracic surgerySurgical treatment of 599 patients with hydatid cysts in the liver and lungs - Eser, Irfan; Sak, Zafer Hasan Ali; Gunay, Samil; Seker, Ahmet; Yalcin, Funda; Cevik, Muazzez; Aydin, Mehmet Salih; Ulas, Turgay; Uzunkoy, Ali; Kurkcuoglu, Ibrahim Can (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Introduction: Hydatid cyst disease is characterized by the occurrence of cysts as a result of the transmission of Tenia echinococcus larvae to humans. The most frequent location is the liver (60-70%). The larvae which fail to attach to the liver pass through the lungs (20-25%), and can be located in all organs and tissues connected to the systemic circulation (10%). They create hydatid cysts in the organs in which they are located. In our multi-center study, we aimed to present different types of surgical treatment, its results, and the associated complications on the basis of a wide series of cases. Material and methods : 599 patients who received surgical treatment were included in our study. The patients’ data from archive records were examined retrospectively. Patients with unusual locations of the cysts (without liver or lung involvement) were excluded from the study. Results : 381 of the patients were women and 218 were men. It was established that the disease was more frequent among women than among men, which was in accordance with the literature [9]. The ratio of women to men was 1.747. The average age was 35.6; the youngest patient was 3, while the oldest was 83. When the patients were evaluated with regard to organ involvement, liver cysts were found in 425 patients, while lung cysts occurred in 236 patients. Both liver and lung involvement was revealed in 62 patients. Conclusions: In the case of lung cysts, surgical treatment is preferred to medical treatment if there are no serious contraindications for operation. Even if only single cysts are found in the liver, lungs, or both of these organs, the stomach and the thoracic space must also undergo radiological screening. One of the main concerns during surgical treatment, in the case of both lung and liver cysts, is protecting the organ parenchyma and removing the cyst without damaging organ function.